Servitization as a Concept for Managing the Development of Small and Medium-sized Enterprises - Lachiewicz Stefan; Matejun Marek; Pietras Paweł; Szczepańczyk Maciej (Management)
The aim of the article is to present the key features, stages, advantages and threats of servitization as a concept for managing the development of small and medium-sized enterprises. A literature review and empirical research carried out in the form of a case study of the medium-sized company Mikomax sp. z o.o. from Poland served to achieve the aim of the article. The obtained results indicate a significant role of servitization in the development of the analyzed company. A phased approach to the implementation of this concept has been identified, requiring a number of changes to be made in the management systems of the enterprise. Servitization is a source of strategic, marketing and financial benefits for the company, and the management plans to further develop servitization activities aimed at expanding its market offer and building a sustainable competitive advantage.